Independence of topological surface state and bulk conductance in three-dimensional topological insulators. Issue 1 (December 2018) - Cai, Shu; Guo, Jing; Sidorov, Vladimir; Zhou, Yazhou; Wang, Honghong; Lin, Gongchang; Li, Xiaodong; Li, Yanchuan; Yang, Ke; Li, Aiguo; Wu, Qi; Hu, Jiangping; et al.
Abstract The archetypical 3D topological insulators Bi2 Se3, Bi2 Te3, and Sb2 Te3 commonly exhibit high bulk conductivities, hindering the characterization of the surface state charge transport. The optimally doped topological insulators Bi2 Te2 Se and Bi2−x Sbx Te2 S, however, allow for such characterizations to be made. Here we report an experimental comparison of the conductance for the topological surface and bulk states in Bi2 Te2 Se and Bi1.1 Sb0.9 Te2 S, based on temperature-dependent high-pressure measurements. We find that the surface state conductance at low temperature remains constant in the face of orders of magnitude increase in the bulk state conductance, revealing in a straightforward way that the topological surface states and bulk states are decoupled at low temperatures, consistent with theoretical models, and confirming topological insulators to be an excellent venue for studying charge transport in 2D Dirac electron systems. Topological insulators: Bulk and boundary decoupled How much do the bulk and surface states of topological insulators mix? New experiments confirm that the answer is "not a lot". Researchers from China, the USA, and Russia led by Liling Sun from the Institute of Physics, Chinese Academy of Sciences, have proved that electronic transport through the protected surface states of 3D topological insulators is independent of that in the bulk states. They find that, at low temperature, the surface state conductance stays constant even as the bulk conductance increases by several orders of magnitude when pressure is applied. Therefore, the two types of states must be decoupled. This is significant because it confirms theoretical predictions and highlights that the surface states of topological insulators are a promising place to study electrical properties of 2D Dirac electrons.